The Effect of Ag Content of the Chitosan-Silver Nanoparticle Composite Material on the Structure and Antibacterial Activity - Solmaz Akmaz; Esra Dilaver Adıgüzel; Muzaffer Yasar; Oray Erguven (Advances in Materials Science and Engineering)
The aim of this study is to investigate the antibacterial properties and characterization of chitosan-silver nanoparticle composite materials. Chitosan-silver nanoparticle composite material was synthesized by adding AgNO3 and NaOH solutions to chitosan solution at 95°C. Different concentrations (0,02 M, 0,04 M, and 0,06 M) of AgNO3 were used for synthesis. Chitosan-silver nanoparticle composite materials were characterized by Transmission electron microscopy (TEM), X-ray diffraction (XRD), ultraviolet (UV) spectrophotometer, and Fourier transform infrared (FTIR) spectrometer techniques. Escherichia coli, Acinetobacter baumannii, Staphylococcus aureus, Enterococcus faecalis, Pseudomonas aeruginosa, and Streptococcus pneumoniae were used to test the bactericidal efficiency of synthesized chitosan-Ag nanoparticle composite materials. The biological activity was determined by the minimum bacterial concentration (MBC) of the materials. Antibacterial effect of chitosan-silver nanoparticle materials was increased by increasing Ag amount of the composite materials. The presence of small amount of metal nanoparticles in the composite was enough to significantly enhance antibacterial activity as compared with pure chitosan.